Penambahan Kelopak Bunga Rosella dalam Penambahan Selai Jambu Biji Merah - Gultom, Adi Hizkia; Herawati, Netti; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study was to obtain the best ratio between red guava pulp with roselle flowerpulp in the making of jam. This study used Completely Randomized Design (CRD) with four treatments and four replications. If the results of the study showed a significant difference between treatments, then continued test using DNMRT test at level 5%. The treatment in this research was the ratio of red guava pulp to roselle petal porridge, respectively PT1 (10: 0), PT2 (9: 1), PT3 (8: 2), and PT4 (7: 3). Parameters observed in this jam were moisture content, ash content, pH, total dissolved solids, sucrose content, and sensory assessment. The best ratio in this research is PT4. The resulting moisture content of 25.01%, ash content of 0.25%, contained pH 3.85, total dissolved solids 76.87%, sucrose content 50.07%, Based on descriptive sensory assessment, the result of colored jam (4, 17), flavor (3.17), smell (3.33) has a texture (4.13) and the overall assessment gives a good impression (6,27). Keywords: jam, red guava, rosella flower petals